Edukasi Ekonomi Sebagai Kunci Pemberdayaan Masyarakat Ngrancang - Fitrahadi, Alfandri; Shalihah, Armatus; Syafa’, Kintan Abelliana Al Masya; Nur Tsani, Muhammad Abrar Imam; Fathurrohman, Muhammad Aditya; Ar Rafi’i, Muhammad Faisal; Amalina, Nisrina Khairunnisa; Rahayu, Septika Dian; Melani, Wina; Adi Putra, Zhulhan Erlangga; Darumurti, Awang (Universitas Muhammadiyah Yogyakarta, 2025)
The main challenges faced by society today are the widespread issue of online gambling among young people, the lack of awareness about safe investment practices, and the underutilization of natural resources and effective marketing strategies. To address these issues, this community service program aims to enhance financial literacy, skills in agricultural product processing, and an understanding of marketing strategies that can improve the competitiveness of local products. The program is conducted through three main seminars: Seminar on Online Gambling and Investment, Seminar on Agricultural Product Processing, and Seminar on Marketing and Packaging. The methods used include presenting materials, interactive discussions, and hands-on practice. The first seminar discusses the negative impacts of online gambling and the importance of safe investments. The second seminar provides training on processing corn into high-value products. The third seminar teaches marketing techniques, packaging design, and product pricing strategies to make them more competitive. The outcomes of this activity are that participants gain a deeper understanding of sound financial management, agricultural processing skills, and effective marketing strategies. With this education, the community is expected to be able to develop agriculture-based businesses, increase income, and expand the reach of local products to a broader market